Application of NFC Technology for Cashless Payment System in Canteen - Evizal Abdul Kadir; Siti Mariyam Shamsuddin; Sri Listia Rosa (IAES Indonesia Section, 2015)
In a campus community, mostly is younger people andstay in University hostel without cooking facilities then have to getfrom canteen for foods and beverages. In office hour with limitedbreak time either breakfast or lunch everyone is rushing to get foodand crowded situation are happen. One of the issues is paymentsystem use manually (cash) and queue at the cashier to pay foods,sometime need to wait a few minute until to get the turn. Cashlesspayment such as token or credit system is implementing in some ofrestaurant and food courts but does not applicable in Universitycanteen that most of customers are students with small transaction,only a few dollars and cents. Nowadays, mobile phone or smartphone is not a luxury thing and most of student carries it for phonecall, message, email, or browsing internet. Most of smart phone alsoembedded with Near Field Communication (NFC) reader inside thephone, thus by using this phone with NFC enable to do paymentsystem at the canteen. The credit is deducted from mobile phonebalance for pre-paid system or billed in monthly for postpaid andthis system have working together to the cellular phone operator.Confirmation on payment system is shows whether customerapprove payment or not then a notification is sent to user.With thissystem be able to overcome several issues such as queue at cashierfor payment and risk of student to carry cash money while buyingfoods.